2012
DOI: 10.1037/a0026969
|View full text |Cite
|
Sign up to set email alerts
|

Video game playing, attention problems, and impulsiveness: Evidence of bidirectional causality.

Abstract: The present study examines video game playing as it relates to attention problems and impulsiveness in a sample of 3,034 children and adolescents from Singapore measured over 3 years. Consistent with previous research, those who spend more time playing video games subsequently have more attention problems, even when earlier attention problems, sex, age, race, and socioeconomic status are statistically controlled. Violent content may have a unique effect on attention problems and impulsiveness, but total time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
208
6
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(246 citation statements)
references
References 22 publications
15
208
6
17
Order By: Relevance
“…Longitudinal studies among children with ASD will be essential to determine whether attention problems contribute to maladaptive video game use, whether problematic video game use leads to attention problems, and whether there are bidirectional influences (as in general population studies). 7 This was also the first study to examine game genre preferences among children with ASD compared with other children. A somewhat greater, though not significantly different, percentage of boys with ASD preferred role-playing games (eg, the Pokémon series) compared with boys with TD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal studies among children with ASD will be essential to determine whether attention problems contribute to maladaptive video game use, whether problematic video game use leads to attention problems, and whether there are bidirectional influences (as in general population studies). 7 This was also the first study to examine game genre preferences among children with ASD compared with other children. A somewhat greater, though not significantly different, percentage of boys with ASD preferred role-playing games (eg, the Pokémon series) compared with boys with TD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that children with ASD spend substantial amounts of time playing video games, [1][2][3] have difficulty disengaging from them, 4 and show higher levels of problematic (addictive) video game use than do children with typical development. 5 Similarly, children with ADHD exhibit greater problematic video game use than do children with TD, 6 and ADHD symptoms are associated with greater time spent on video games 7,8 and with greater problematic game use. 8 Han et al 9 also found a reduction in problematic video game use among children with ADHD after an 8-week trial of methylphenidate.…”
mentioning
confidence: 99%
“…However, those who participated in gambling and video game playing, respectively, were more impulsive than those who did not. Gambling and video game playing, and pathological gambling and gaming, have been linked previously with impulsivity (e.g., Gentile et al, 2011;Gentile, Swing, Lim, & Khoo, 2012;Littel et al, 2012;Walther et al, 2012;Zuckerman, 2007). Problem gamblers tend to act on the spur of the moment; they show difficulty with planning and thinking carefully, and often discount future, large rewards in favour of immediate, smaller ones (Ledgerwood et al, 2009).…”
Section: Factors That Affect Problem Gambling and Gamingmentioning
confidence: 99%
“…Indeed, it has been observed that early experiences may influence the development of impulsiveness (Anda et al, 2006;Perry, 2009). In addition, it has been suggested that impulsiveness may have a bidirectional relationship to the use of video games (Gentile et al, 2012), as shown by the results of a longitudinal study in which impulsiveness predicts video game abuse (Gentile et al, 2011). In the development of adolescents, in which impulsiveness acquires a priority dimension, limiting the use of video games to weekends may provide an exercise for the control of the impulsiveness of minors.…”
Section: Impulsiveness Use Of Video Games and Addictionmentioning
confidence: 96%